Upaya Pemberdayaan Remaja Berbasis Daring sebagai Inovasi Pencegahan Covid-19 di Desa Loram Wetan Kabupaten Kudus - Mayditania Intan Bunga Pratiwi; Defi Pamelasari (Jurnal Studi Inovasi, 2021)
Covid-19 has spread in 223 countries until now cases of infection are also increasing. Various efforts to prevent Covid-19 have been implemented. However, adolescents are often found to still violate the rules, this is caused by the lack of public knowledge related to Covid-19, indifferent behaviour and attitudes, and the lack of special socialization to teenagers resulting in not optimal Covid-19 prevention programs. This empowerment was carried out in RT 05 RW 03 Loram Wetan Village which lasted for 3 weeks in July-August 2020. The activity was successful and the enthusiasm of the participants was very good in the process of providing education which was carried out online via Whatsapp. Media education used posters, booklets and leaflets. To determine changes in knowledge, attitudes and behaviour, pre-test and post-test questionnaires were given which were filled out by 28 adolescents who participated in the activity, the results were analyzed using the Wilcoxon test. There was a significant change in knowledge (p-value < 0.05), but there was no significant change in attitudes and behaviour about Covid-19 (p-value > 0.05). However, both knowledge, attitude, and behaviour are increased.